2000
DOI: 10.1177/000992280003901003
|View full text |Cite
|
Sign up to set email alerts
|

Problem Identification in Apparently Well Neonates: Implications for Early Discharge

Abstract: The frequency, time of identification, and type of problems of newborns in an urban indigent population were prospectively studied during their hospital stay to evaluate feasibility of early hospital discharge. Eight percent (563) of 7,021 term and near-term low-risk infants developed one or more predefined problems. Of those with problems, 42.1% received therapy and/or a higher level of care. Tachypnea, temperature instability, and cyanotic episodes were the most frequently treated problems. Nearly 69% of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
0
18
0
2
Order By: Relevance
“…Facility-based published data suggested that the majority of health problems, including jaundice, infection, feeding difficulties, birth defects, and respiratory problems may not be detected until after the initial assessment. Late preterm infants are biologically vulnerable to experiencing temperature instability, hypoglycemia, apnea and bradycardia, sepsis, hyperbilirubinemia, and feeding difficulties [22][23][24]. Similarly, respiratory distress syndrome (24.2%), sepsis (18.2%), and premature (13.6%) and neonatal jaundıce (12.1%) were the leading causes of direct neonatal deaths in our study, showing a high prevalence of infectious diseases.…”
Section: Discussionmentioning
confidence: 58%
“…Facility-based published data suggested that the majority of health problems, including jaundice, infection, feeding difficulties, birth defects, and respiratory problems may not be detected until after the initial assessment. Late preterm infants are biologically vulnerable to experiencing temperature instability, hypoglycemia, apnea and bradycardia, sepsis, hyperbilirubinemia, and feeding difficulties [22][23][24]. Similarly, respiratory distress syndrome (24.2%), sepsis (18.2%), and premature (13.6%) and neonatal jaundıce (12.1%) were the leading causes of direct neonatal deaths in our study, showing a high prevalence of infectious diseases.…”
Section: Discussionmentioning
confidence: 58%
“…İkinci günden sonra %5.6 bebekte problem gelişebilmektedir (16). Erken taburculukta geriye tekrar yatış oranı önemlidir.…”
Section: Sezaryenunclassified
“…The historical success of such alternative care provisions as home visits common during World War II suggest that the e¡ectiveness of follow-up programs in the current health care environment needs to be studied. The timing of follow-up care may be more critical than the timing of hospital discharge (Jackson et al, 2000). As such, more information is needed to evaluate the quantity and quality of follow-up care and its e¡ects on maternal and newborn outcomes.…”
Section: Implications and Recommendationsmentioning
confidence: 99%